2011
DOI: 10.1007/s11420-011-9219-y
|View full text |Cite
|
Sign up to set email alerts
|

Locking and Non-locking Constructs Achieve Similar Radiographic and Clinical Outcomes for Internal Fixation of Intra-articular Distal Humerus Fractures

Abstract: Background: Locking plates have been used increasingly for the management of distal humerus fractures. Studies that compare patient-centered outcomes between locking and non-locking fixation for distal humerus fractures are lacking. Questions/Purposes: The purposes of this study were to (1) determine whether locking plates offered superior fixation compared with non-locking plates for distal humerus fractures, (2) determine whether the use of locking plates was associated with fewer complications, and (3) dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A comparison of non-locking and locking plate constructs in biomechanical study has been done by Komer et al In which they found that the stiffness of the construct was no different if arranged in the same configuration [9] . Another study by the same group compared orthogonal constructs using conventional reconstruction plates, locking cornpression plates, and precontoured distal humerus locking plates in cadaveric specimens of varymg bone mineral densities and they concluded that fixation with either locking or nonlocking plates is acceptable in patients with good bone mineral density, but locking plates could prove to be more effective 111 patients with lower bone mineral density [10] .…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of non-locking and locking plate constructs in biomechanical study has been done by Komer et al In which they found that the stiffness of the construct was no different if arranged in the same configuration [9] . Another study by the same group compared orthogonal constructs using conventional reconstruction plates, locking cornpression plates, and precontoured distal humerus locking plates in cadaveric specimens of varymg bone mineral densities and they concluded that fixation with either locking or nonlocking plates is acceptable in patients with good bone mineral density, but locking plates could prove to be more effective 111 patients with lower bone mineral density [10] .…”
Section: Resultsmentioning
confidence: 99%
“…19,25 In one study, use of locking plate fixation (n = 65) compared to unlocked constructs (n = 31) was shown to be no different with regard to rates of reoperation. 26…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical evidence leading to this conclusion resembles that for parallel plating, in that locking screws create a stiffer construct in some but not all testing environments 13 . Clinically, however, Berkes et.al 14 retrospectively reviewed 96 AO type 13C distal humerus fractures, of which 65 underwent plate fixation with locking screws and 31 with non locking screws, and found no difference in the two groups in rates of non union, infection and re operation. The critical factors for successful outcome remain those advocated earlier by Cassebaum 15 .…”
Section: Jmscr Vol||07||issue||06||page 905-915||june 2019mentioning
confidence: 99%